2013
DOI: 10.1016/j.jcin.2012.12.122
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Mechanical Unloading With Left Ventricular Assist Devices After Acute Myocardial Infarction Conserves Calcium Cycling and Improves Heart Function

Abstract: Objectives This study sought to demonstrate that short-term cardiac unloading with a left ventricular (LV) assist device (LVAD) after acute myocardial infarction (MI) can conserve calcium cycling and improve heart function. Background Heart failure secondary to MI remains a major source of morbidity and mortality. Alterations in calcium cycling are linked to cardiac dysfunction in the failing heart. Methods Adult Dorsett hybrid sheep underwent acute MI and were mechanically unloaded with an axial-flow LVAD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 27 publications
1
27
1
Order By: Relevance
“…Our previous study (5) focused on the effects of LVAD support on regional LV remodeling. Specifically, partial LV unloading with the Impella 5.0 LVAD for only 2 weeks post-MI was found to reduce diastolic strain (i.e., local cardiomyocyte stretch/preloading) in the MI-adjacent zone at up to 12 weeks following MI.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous study (5) focused on the effects of LVAD support on regional LV remodeling. Specifically, partial LV unloading with the Impella 5.0 LVAD for only 2 weeks post-MI was found to reduce diastolic strain (i.e., local cardiomyocyte stretch/preloading) in the MI-adjacent zone at up to 12 weeks following MI.…”
Section: Resultsmentioning
confidence: 99%
“…These are described in detail in (5). In brief, adult Dorsett hybrid sheep (53.2 ± 0.9 kg) were used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Heerdt et al (15) found that restored contractile function after LVAD correlated with SERCA2a improvement, which has led to novel therapeutic avenues supplementing SERCA2a to the failing myocardium (40). A recent study in sheep with myocardial infarction confirmed preserved SERCA2a levels, calcium cycling, and cardiac function with short-term mechanical support (37). NCX1 levels, which act to compensate decreased cytoplasmic clearance of Ca 2ϩ by SERCA2a (18), were also restored by LVAD support, consistent with animal and human models of HF (8).…”
Section: Discussionmentioning
confidence: 99%
“…9 MCADs exert their beneficial effect through multiple pathways and may yield reverse remodeling, conserve calcium cycling, and short-term mechanical unloading. 10,11 The Interagency Registry for Mechanically Assisted Circulatory Support (INTERMACS) analyzed 99 women with PPCM between 2006 and 2012. 4 The ventricular assist devices that were used in the INTERMACS registry included total artificial heart, continuous and pulsatile left ventricular assist devices and biventricular assist devices.…”
Section: Discussionmentioning
confidence: 99%